2021
DOI: 10.1515/med-2021-0001
|View full text |Cite
|
Sign up to set email alerts
|

CircRNA circ_0004370 promotes cell proliferation, migration, and invasion and inhibits cell apoptosis of esophageal cancer via miR-1301-3p/COL1A1 axis

Abstract: Background The aim of this study was to investigate the circ_0004370 expression in EC, its effects on cell proliferation, apoptosis, migration, invasion, and epithelial–mesenchymal transition (EMT) process, and the underlying regulatory mechanisms in EC. Methods The protein levels of COL1A1 and EMT-related proteins were detected by western blot. The role of circ_0004370 on cell viability, proliferation, and apoptosis was anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…Studies have shown that miR-1301-3p plays a dual role in tumor progression and can be used as a prognostic biomarker and therapeutic target for some malignant tumors [ 21–24 ]. In addition, miR-1301-3p was sponged by Circ_0004370, CircRNA MYLK and participated in cancer progression [ 25 , 26 ]. Here, our results showed that miR-1301-3p mimic could partially reverse the effect of hsa_circ_0008583 overexpression on HCC cell progression, which indicated that hsa_circ_0008583 played a carcinogenic role in HCC by sponging miR-1301-3p.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that miR-1301-3p plays a dual role in tumor progression and can be used as a prognostic biomarker and therapeutic target for some malignant tumors [ 21–24 ]. In addition, miR-1301-3p was sponged by Circ_0004370, CircRNA MYLK and participated in cancer progression [ 25 , 26 ]. Here, our results showed that miR-1301-3p mimic could partially reverse the effect of hsa_circ_0008583 overexpression on HCC cell progression, which indicated that hsa_circ_0008583 played a carcinogenic role in HCC by sponging miR-1301-3p.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has demonstrated that COL1A1 and COL4A1 are associated with several clinical parameters, including TNM staging, lymph node metastasis, and tumor invasion depth in gastric cancer patients (48). COL1A1 has been reported to be highly expressed in EC cells, and upregulation of COL1A1 has been associated with cell proliferation, invasion, and apoptosis (49). DCN, a small stromal proteoglycan, is a member of the SLRP gene family (50), and Bozoky et al found that its expression is consistently decreased in the tumor microenvironment of various cancers (51).…”
Section: Discussionmentioning
confidence: 99%
“…miR-1301 is involved in the biological processes of tumor cell proliferation, migration, invasion, and apoptosis by regulating multiple downstream genes (Figure 1). In all tumor types involved in miR-1301, the abnormal expression of miR-1301 can affect the proliferation of tumor cells by affecting cell cycle and apoptosis (1,7,9,12,16,17,24,(26)(27)(28)(29)(33)(34)(35)(36). Metastasis is characterized by cancer cells invading the basement membrane into the adjacent matrix, then invading and surviving into the circulatory system (including blood and lymphatic tissue), and extravasation to distant tissues.…”
Section: The Aberrant Expression Of Mir-1301 In Cancermentioning
confidence: 99%
“…In cervical cancer, circRNA MYLK up-regulates the expression of RHEB through sponging miR-1301 and promotes tumorigenesis (33). In esophageal cancer, Circ_0004370 up-regulates COL1A1 through sponging miR-1301 to promote the occurrence and development of esophageal cancer (12). In esophageal squamous cell carcinoma (ESCC), SOX2 binds to the MIAT promoter region to promote CircRNA and lncRNA can be used as the ceRNA of miR-1301, which promotes the expression of downstream target genes through sponging miR-1301, and participates in the occurrence and development of tumors.…”
Section: The Mir-1301-related Cerna Networkmentioning
confidence: 99%